UPAYA PENINGKATAN KUALITAS PENYUSUNAN RPP MELALUI MONITORING DAN EVALUASI PELAKSANAAN PROGRAM MADRASAH DI MAN 1 PASAMAN BARAT - JUFRI JUFRI (STKIP Pesisir Selatan, 2019)
Based on observations that researchers have conducted teachers at MAN 1 Pasaman Barat, it was found that the ability of teachers in preparing lesson plans is still low. The purpose of this study is to describe and obtain information about the preparation of lesson plans by the teacher. This research is a madrasa action research. Research procedures in this study include planning, action, observation and reflection. This research consisted of two cycles with four meetings. The research subjects consisted of 4 MAN 1 Pasaman Barat teachers. Research data were collected using observation sheets. Data were analyzed using percentages. The results showed that monitoring and evaluation could improve the preparation of teacher's lesson plans in MAN 1 Pasaman Barat. This is evidenced by the evaluation and monitoring can improve the quality of the preparation of teacher RPP in MAN 1 Pasaman Barat from cycle I to cycle II. The average teacher's ability to improve the making of lesson plans in the first cycle is 51.39 with less categories, in the second cycle is 85.46 Good.